HUBUNGAN KONSEP DIRI DENGAN PRESTASI BELAJAR PESERTA DIDIK DIKELAS XI SMA NEGERI 1 SUTERAKABUPATEN PESISIR SELATAN - Anjani, Delpi - (Bimbingan dan Konseling, 2014)
This research is motivated by the existence of learners who prefer to own. Purpos of the research describe: 1) an overview of self-consep, 2) description of student achievement, 3) The relationship of self-concept and academic achievement. quantitative descriptive researceh, the population of students in class XI, amounting to 250 people and 71 samples. Sampling using simple random sampling technique. Data collection tools such as questionnaires and documentation in the form of grades. Analyzed data on self-concept and academic achievement using the data analysis techniques percentage, hypotheses testing to examine the relationship between self-concept and academic achievement using the pearson product moment correlation formula, the calculation using SPSS version 16.0. Data analysis results obtained: (1) self-consept less well categorized learners. (2) academic achievement of student in middle category. (3) The relationship of self-concept and academic achievement of students obtained 0.273 count r> r table 0.234. So based on this study the relationship between self-concept and academic achievement of students.